N,N′-Bis(4-aminobenzyl)oxalamide - Juan Saulo Gonzalez-Gonzalez (Acta Crystallographica Section E, 2011)
In the title compound, C16H18N4O2, the two carbonyl groups are in an antiperiplanar conformation with an O=C—C=O torsion angle of 173.86 (17)°. In the crystal, a pair of intermolecular N—H...O hydrogen bonds, forming an R22(10) ring motif, connect the molecules into an inversion dimer. The dimers are further linked by N—H...N and C—H...π interactions, forming a zigzag chain along the b axis.